Enhanced hydrogen storage capacity of Ni/Sn-coated MWCNT nanocomposites. (15th January 2018) - Varshoy, Shokufeh; Khoshnevisan, Bahram; Behpour, Mohsen
Abstract: The hydrogen storage capacity of Ni–Sn, Ni–Sn/multi-walled carbon nanotube (MWCNT) and Ni/Sn-coated MWCNT electrodes was investigated by using a chronopotentiometry method. The Sn layer was electrochemically deposited inside pores of nanoscale Ni foam. The MWCNTs were put on the Ni–Sn foam with nanoscale porosities using an electrophoretic deposition method and coated with Sn nanoparticles by an electroplating process. X-ray diffraction and energy dispersive spectroscopy results indicated that the Sn layer and MWCNTs are successfully deposited on the surface of Ni substrate. On the other hand, a field-emission scanning electron microscopy technique revealed the morphology of resulting Ni foam, Ni–Sn and Ni–Sn/MWCNT electrodes. In order to measure the hydrogen adsorption performed in a three electrode cell, the Ni–Sn, Ni–Sn/MWCNT and Ni/Sn-coated MWCNT electrodes were used as working electrodes whereas Pt and Ag/AgCl electrodes were employed as counter and reference electrodes, respectively. Our results on the discharge capacity in different electrodes represent that the Ni/Sn-coated MWCNT has a maximum discharge capacity of ∼30 000 mAh g −1 for 20 cycles compared to that of Ni–Sn/MWCNT electrodes for 15 cycles (∼9500 mAh g −1 ). By increasing the number of cycles in a constant current, the corresponding capacity increases, thereby reaching a constant amount for 20 cycles.